Application of Person-Material-Process combined with management checklist in rescue and emergency care of critically ill children in the Department of Pediatrics (PMP结合清单管理在儿科急诊急危重症患儿抢救中的应用) - HAN Lingzhi (韩玲芝); XIONG Xiaoju (熊晓菊); YU Genzhen (余艮珍); ZHU Shan (朱杉) (Association of Integrative Nursing, 2022)
Objective To investigate the Person-Material-Process (PMP)combined with management checklist in rescue and emergency care of critically ill children in the Department of Pediatrics. Methods A total of 268 pediatric patients who were successfully rescued in the emergency room between Jan and December, 2020 were selected as the control group. Another 283 cases of rescued children in the emergency room between Jan and December, 2021 were recruited as the observation group. A routine management process of rescue and emergency care was adopted in the control group. In the observation group, the PMP management combined with management checklist was used to improve the quality of management from three aspects: nursing training, adverse events associated with instruments and drugs, rescue and emergency care procedures. The accuracy rate of procedure in rescue and incidence of adverse events associated with rescue materials were observed and compared between two groups. Results The accuracy rate of rescue procedure was 98. 94%(280/283)in the observation group, which was higher than 91. 42%(245/268) in the control group (P＜0. 01). The incidence of adverse events associated with rescue instruments and lack of rescue goods in the observation group were lower than those in the control group (P＜0. 01). Conclusion Implementation of PMP combined with management checklist is potentially effective to reduce the risk of adverse events in the rescue and emergency care, and ensure the safety of critically ill children. (目的 探讨PMP结合清单管理在儿科急危重症患儿抢救中的效果。方法 将2020年1月-12月在医院儿科急诊进行抢救的患儿268例作为对照组, 2021年1月-12月在医院儿科急诊进行抢救患儿283例为观察组。对照组采取常规急救管理流程对危重患儿进行抢救和护理, 观察组在抢救过程中, 采用PMP结合清单管理, 从护士培训、仪器设备物品药品管理以及儿科常见急危重症抢救流程三个方面进行干预。比较两组抢救人员处置行为正确率, 以及与抢救物品、仪器、药品相关的不良事件发生率的差异。结果 观察组抢救人员处置行为正确率98. 94%(280/283), 高于对照组的91. 42%(245/268), 差异有统计学意义(P＜0. 01)。观察组仪器设备功能相关不良事件和物品不足发生率均低于对照组(P＜0. 01)。结论 PMP结合清单管理能显著降低急危重症患儿抢救中不良事件的发生率, 保证患儿安全。)